ANALISIS KEMAMPUAN BERPIKIR KREATIF DALAM MENYELESAIKAN SOAL MATEMATIKA HOTS MELALUI GAYA KOGNITIF - Fafria Fari Hastuti; Sri Sutarni (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
The purpose of this study is to explain the ability to think creatively when working on HOTS questions based on reflective and impulsive cognitive learning styles. The research was conducted using a qualitative descriptive method. The research subjects were class VII students of SMP Negeri 1 Polokarto with reflective and impulsive characteristics. The research subjects were selected through the Matching Familiar Figures Test (MFFT). The method used in conducting this research is The Matching Familiar Figure Test (MFFT), test sheets, and interview sheets. MFFT sheets to determine students' cognitive styles, test sheets to assess students' original thinking abilities, and interview sheets to complete information on test results. The stages of simplification, presentation, and drawing conclusions are used in analyzing the data. The results of the study proved that students' creative thinking abilities in solving HOTS questions with a reflective cognitive style were able to meet the indicators for aspects of flexibility, originality, and detail, while the aspects of fluency were still not met. Meanwhile, students who have an impulsive cognitive style do not meet the indicators of flexibility and detail aspects because students with an impulsive cognitive style can only answer questions in one way and have not answered the questions in detail.